Research of the primary metabolites of Astragalus dasyanthus herb - Khvorost, Olga; Zudova, Yehenia (Annals of Mechnikov’s Institute, 2023)
Introduction. One of the directions of complex tepary of hypertension is the application of medicinal plant raw materials and preparations based on them. One of these plants is Astragalus dasyanthus Pall. Fabaceae legume family. It is a perennial herbaceous plant. The raw material is grass. The chemical composition of raw materials is quite diverse: polysaccharides arabin and basorin, mucus, organic acids, triterpene saponins (cycloartane derivatives), flavonoids (kaempferol, quercetin, isorhamnetin and their glycosides), mineral compounds (compounds of iron, calcium, aluminum, phosphorus, magnesium, sodium, barium, silicon, strontium, molybdenum, vanadium and manganese, selenium). The aim of the work is to study the component composition of the primary metabolites of the herb A. dasyanthus grown in Ukraine. Materials and methods. Grass was harvested from biennial cultivated plants in the phase of mass flowering in 2021 in the Kharkiv region.The determination of free monosaccharides in plant material was carried out by the GC/MS method. Chromatographic separation was performed on an Agilent 6890N/5973inert gas chromatography-mass spectrometric system (Agilent technologies, USA). HP-5ms capillary column (30m×0.25mm×0.25mkm, Agilent technologies, USA). The evaporator temperature is 250 °C, the interface temperature is 280 °C. The separation was carried out in the temperature programming mode - the initial temperature of 160 °C was maintained for 8 min, then raised with a gradient of 5 °C/min to 240 °C. The final temperature was maintained for 6 minutes. A sample with a volume of 1 μl was injected in the mode of flow division 1:50. Detection was carried out in SCAN mode in the range (38-400 m/z). Identification of monosaccharides of the studied mixture was carried out by comparing the retention times of standard monosaccharides and using the NIST 02 mass spectrum library. Quantitative analysis was carried out by adding a solution of the internal standard to the studied samples. Sorbitol solution was used as an internal standard. Chromatographic separation was performed on an Agilent 1200 liquid chromatograph (Agilent technologies, USA). Zorbax AAA column 150 mm long, 4.6 mm internal diameter, 3 μm sorbent grain diameter. Mobile phase A - 40 mM Na2HPO4 pH 7.8; B - ACN:MeOH: water (45:45:10, v/v/v). Results and discussion. Free sugars are represented by D-mannose, D-glucose and sucrose. The content of sucrose (3.39±0.01 mg/g) is almost 10 times higher than the content of D-mannose (0.37±0.01 mg/g), D-glucose (1.19±0.02mg/g) - almost three times. In addition, the polyols (+)-pinitol and myo-inositol were invented. The bound carbohydrates of A. dasyanthus herb are represented by 6 monosaccharides, 2 polyols and 1 disaccharide. Significant amounts were found for D-glucose (20.09±0.02 mg/g) and (+)-pinitol (25.73±0.01 mg/g). Sophorose (β-D-glucopyranosyl-(1,2)-α-D-glucopyranose). Free and bound amino acids are represented by 12 identical compounds. The content of L-aspartic acid, L-serine, L-histidine, L-threonine, L-valine, L-isoleucine and L-proline is higher in the free state, the rest in the bound state. Conclusions. 1. The component composition of primary metabolites: free and bound carbohydrates, free and bound amino acids of the herb A. dasyanthus grown in Ukraine was studied. 2. It was established that in the free state it contains 2 monosaccharides, 1 disaccharide and 2 polyols, in the bound state - 2 monosaccharides, 1 disaccharide and 2 polyols. The high content of polyol: (+)-pinitol correlates with the use of this raw material as an antioxidant and metabolism normalizer. 3. The amino acid composition is represented by 12 compounds both in free and bound state. L-Aspartic acid dominated in the free state, glycine in the bound state. 4. The obtained research results are a fragment of the systemic pharmacognostic study of the herb A. dasyanthus, grown in Ukraine, and testify to the appropriateness of creating preparations based on it. Keywords: A. dasyanthus, herb, primary metabolites, free and bound carbohydrates, free and bound amino acids